Thrombocytopenia as a predictor of severe acute kidney injury in patients with heat stroke. (16th March 2015) - Fan, Heng; Zhao, Yu; Zhu, Jian-Hua; Song, Fu-Chun; Ye, Ji-Hui; Wang, Zhi-Yu; Le, Jian-Wei
Abstract: Background : Abnormalities of blood system often occur several days before acute kidney injury (AKI) in patients with heat stroke (HS). We aimed to investigate the prevalence and prognostic value of the early hematological markers in patients with AKI induced by HS. Methods : In a retrospective cohort study, we analyzed the case records of 176 patients with HS and evaluated the hematological markers for early prediction and risk classification in the patients with AKI. Results : Of 176, 103 (58%) HS cases developed AKI, and men comprised more than half (75%) of the sample population. The nadir platelet count significantly correlated with the levels of peak serum creatinine ( r = −0.608, p < 0.01) and blood urea nitrogen ( r = −0.546, p < 0.01), and the length of hospital stay ( r = −0.393, p < 0.01). The areas under the receiver operating characteristic curves (AU-ROC) indicated the prognostic accuracy of hematological markers, AU-ROC was significantly higher with the nadir platelet count than that with the admission platelet count (AU-ROC of the nadir platelet: 0.73; 95% CI: 0.67–0.82; vs. AU-ROC of the admission platelet: 0.67; 95% CI: 0.59–0.75; p < 0.01). Multiple logistic regression results indicated that the nadir platelet count (adjusted ORs: 37.92; 95% CI: 2.18–87.21; p < 0.01) was independent predictor of AKI in HS. Conclusion : The high mortality observed in HS complicated with AKI, and among the various hematological parameters assessed, thrombocytopenia is associated with AKI induced by HS independently.